Radiating Impact of WTO on Its Members' Legal System : the Chinese Perspective. - Wang, Guiguo (Pocket Books of the Hague Academy of International Law//Les livres de poche de l'Académie de droit international de La Haye., 2011)
The World Trade Organization ("WTO") resulted from globalization, through which national law provisions are internationalized and international norms are domesticated. The WTO does not permit reservation by its members who are obliged to ensure the compliance of their laws, policies and other measures. Once a member is found to have violated its obligations, it must rectify the non-compliance measures to avoid retaliation. The quasi-automatic approval procedure of the WTO Dispute Settlement Body has proved to be effective in ensuring the compliance by members and consistency of interpretation.